Instrumentation of financial regulation of the electric vehicle market on the example of leading automobile manufacturers - SYDOROVYCH, Olena; SHUKLINOV, Roman (Scientific journal «World of Finance», 2019)
Introduction. The market of electric cars has a long history of its formation. The devastating impact of human management on the environment, the acute need to minimize environmental risks and threats identified by the United Nations Framework Convention on Climate Change in 1992, created the basis for the rapid development of the market for electric vehicles in the early twenty-first century. The purpose of the paper is an analysis of tools for financial regulation of the electromotive market on the example of leading automotive manufacturers. In particular, the main research interests are the main directions of application of financial regulation instruments and methods, their dependence on long-term goals of application, and analysis of probable variants of introduction of foreign experience in Ukrainian realities in order to stimulate the development of the market of electric vehicles. Results. The specifics of the financial regulation of the electromotive market are the focus on achieving the long-term goals of the sustainable development concept. The financial instruments for regulating demand for electric vehicles include: subsidizing, lending, tax incentives. Conclusions. In Ukraine, the market of electric vehicles is at the stage of formation. The main factors for stimulating its development include: the application of tax privileges over the past three years, namely the application of a zero import duty rate, exemption from VAT, reduced excise tax rates, as well as significant operational advantages of electric vehicles.